A Comparative Study of Potassium Hydroxide versus CO2 Laser Vaporization in The Treatment of Female Genital Warts: A Controlled Clinical Trial - Nasrin Asadi; Ensie Hemmati; Golnaz Namazi; Mahnaz Pakniat Jahromi; Zahra Sarraf; Nader Pazyar; Alireza Salehi (Shiraz University of Medical Sciences, 2016)
Background: Genital warts are the most common viral sexually transmitted disease affecting 1% of the population. A prospective, open-label controlled trial was performed to compare topical 5% potassium hydroxide (KOH) solution with CO2 laser in the treatment of female genital warts. Methods: Seventy patients were enrolled in the study after convenience sampling. Right-sided lesions of the patients were treated by CO2 laser every 3 weeks. The left-sided lesions of the same patients were treated by topical 5% KOH solution twice a day using a toothpick with cotton wrap on the tip. The patients were visited at 3, 6, and 9 weeks after initiation of the treatment and followed up for 6 months after the last visit. Results: Out of seventy patients, sixty three completed the study and were analyzed. A total of 56 KOH treated-patients (88.9%) showed complete response. On the other hand, 56 laser-treated patients (88.9%) presented complete clearing of the lesion. There was not any difference in response to both modalities of treatment. Complications of KOH solution and CO2 laser were 24% and 19% respectively (P>0.05), but serious adverse events were not observed. The patients under KOH treatment displayed a recurrence rate of 11.1% (7 cases), while the same patients with CO2 laser therapy demonstrated a recurrence rate of 7.9% (5 cases) (P=0.54). Conclusion: Topical 5% KOH solution was as effective as CO2 laser in the treatment of female genital warts. There was not any serious complication in the application of KOH solution. This could be used as a new treatment for genital warts.